2022
DOI: 10.1002/jssc.202101007
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced capillary zone electrophoresis in cyclic olefin copolymer microchannels using the combination of dynamic and static coatings for rapid analysis of carnosine and niacinamide in cosmetics

Abstract: Cosmetics that have medicinal effects, including anti-inflammatory and antioxidant, have become a daily care routine consumption. The peptide additives, such as carnosine and nicotinamide, were frequently used to realize these medicinal effects. To accomplish rapid and effective quantitation of carnosine and niacinamide in cosmetics, capillary zone electrophoresis was executed in cyclic olefin copolymer microchips having both dynamic and static coatings. The static coating of cyclic olefin copolymer microchann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Peptide and protein sorption to the inner surface of the separation compartment and EOF regulation represent serious problems also in their CE analyses in glass/quartz or plastic microchips. Dynamic coating of cyclic olefin copolymer microchannels with SDS and static coating of these microchannels with BSA suppressed the sorption of dipeptide carnosine (β‐Ala‐ l ‐His) and enabled the determination of this peptide and niacinamide in cosmetic preparations [121].…”
Section: Suppression Of Peptide Adsorption and Regulation Of Eofmentioning
confidence: 99%
“…Peptide and protein sorption to the inner surface of the separation compartment and EOF regulation represent serious problems also in their CE analyses in glass/quartz or plastic microchips. Dynamic coating of cyclic olefin copolymer microchannels with SDS and static coating of these microchannels with BSA suppressed the sorption of dipeptide carnosine (β‐Ala‐ l ‐His) and enabled the determination of this peptide and niacinamide in cosmetic preparations [121].…”
Section: Suppression Of Peptide Adsorption and Regulation Of Eofmentioning
confidence: 99%
“…Traditional cosmetic composition testing mostly relies on instrumental analysis methods such as UV spectrophotometry, high-performance liquid chromatography (HPLC), capillary electrophoresis, animal experiments as in vivo efficacy evaluation methods, and two-dimensional (2D) cell models as in vitro testing methods 2 6 . Although the test techniques are easy to operate and inexpensive, they also have many drawbacks, such as the high consumption of organic reagents in the pretreatment process, low detection throughput, and a long analysis cycle 7 – 10 .…”
Section: Introductionmentioning
confidence: 99%
“…To convert the species to a detectable form, they used a time-consuming chemiluminescence reaction between hydrogen peroxide and N-(4-aminobutyl)-N-ethylisoluminol-labelled peptides in the presence of adenine and Co 2+ [21]. Fresta et al reported the use of fluorogenic reagent naphthalene-2,3-dicarboxaldehyde to quantify intracellular carnosine in macrophage cell lysates [22], and Chen et al analyzed 4-fluoro-7-nitro-2,1,3-benzoxadiazole labeled L-carnosine and niacinamide in cosmetics [23]. Additional simplification of MCE analysis was achieved by integrated capacitively coupled contactless conductivity detection (C 4 D).…”
Section: Introductionmentioning
confidence: 99%